Gross Morphological Variation of Luminal Diameter of the Trachea in Different Age and Sex Groups of Bangladeshi Cadavers (Journal of Enam Medical College, 2017)
Background: The tracheobronchial tree is a branched distribution system that carries air from the trachea down to the acini which are the gas exchange units of the lung. In the trachea air speed is high and the airway is particularly vulnerable to obstruction by foreign bodies and tumors. The study of the morphological variations of luminal diameter of the trachea is of profound clinical importance as it may help the clinicians for smooth conduction of some maneuvers like endotracheal intubation and bronchoscopic procedure. It also helps the surgeons to deal with resection and reconstruction of the trachea.Objective: The present study was carried out to establish a Bangladeshi standard regarding the luminal diameter of the trachea and to minimize the dependency on foreign standards.Materials and Methods: This cross sectional descriptive study was performed on 70 post mortem human trachea (44 male and 26 female) to find out the difference in luminal diameter of the trachea of Bangledeshi people in relation to age and sex. The specimens were collected from the morgue in the department of Forensic Medicine, Mymensingh Medical College, Mymensingh by purposive sampling technique. All specimens were grouped into three groups according to age ? Group A, B and C. Dissection was performed according to standard autopsy techniques. The trachea was cut horizontally through the upper border of the 5th tracheal ring and the luminal diameter was measured. The average diameter was expressed in centimeter. All data were recorded in the predesigned data sheet and statistical analysis was done using computer based statistical package, SPSS to evaluate the significance of variance between the different findings.Results: In the present study the maximum luminal diameter of the trachea was 1.65 in Group A, 2.05 in Group B and 1.85 cm in Group C. The minimum luminal diameter of the trachea was 0.7 cm in Group A, 0.85 cm in Group B and in Group C 0.85 cm. The mean (±SD) luminal diameter of the trachea was 1.24 ± 0.3, 1.39 ± 0.3 and 1.29 ± 0.23 cm in Group A, B and C respectively. The maximum mean luminal diameter of the trachea was in Group B (1.39 cm) and minimum was in Group A (1.24 cm). The mean difference of luminal diameter of the trachea between groups was statistically non significant at p>0.5 level. The maximum mean (±SD) luminal diameter of the trachea was 1.50 ± 0.3 cm in male in Group B and minimum mean (±SD) luminal diameter of the trachea was 1.17 ± 0.26 cm in female in Group C. The mean luminal diameter of the male trachea was found to be greater than that of the female trachea among the age group. Mean difference between sexes in Group B was statistically highly significant at p